2020
DOI: 10.1177/2374373520952975
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Telehealth Experience of Patients With COVID-19 Symptoms: Recommendations on Best Practices

Abstract: Positive patient experiences are associated with illness recovery and adherence to medication. To evaluate the virtual care experience for patients with COVID-19 symptoms as their chief complaints. We conducted a cross-sectional study of the first cohort of patients with COVID-19 symptoms in a virtual clinic. The main end points of this study were visit volume, wait times, visit duration, patient diagnosis, prescriptions received, and satisfaction. Of the 1139 total virtual visits, 212 (24.6%) patients had COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 12 publications
0
31
0
3
Order By: Relevance
“…Patient experience in the telehealth space may be influenced by various factors such as gender, the telehealth modality used, and the specialty of the visit (6). Similarly, provider telehealth competencies play an important role in how patients evaluate their telehealth experience such that telehealth visits that are short or the patient cannot clearly see the provider have lower satisfaction scores.…”
Section: Discussionmentioning
confidence: 99%
“…Patient experience in the telehealth space may be influenced by various factors such as gender, the telehealth modality used, and the specialty of the visit (6). Similarly, provider telehealth competencies play an important role in how patients evaluate their telehealth experience such that telehealth visits that are short or the patient cannot clearly see the provider have lower satisfaction scores.…”
Section: Discussionmentioning
confidence: 99%
“…Schwamm et al implemented intercoms to allow for virtual interaction with patients on the ward, however due to time constraints, were not able to design a formal study on the patient experience of engaging virtually (4). The study by Khairat et al were the first study to investigate the patient experience of an on-demand virtual clinic for COVID-19-positive patients based in the United States (3). The study found that clinic wait times in particular had a significant impact on patient experience.…”
Section: Introductionmentioning
confidence: 99%
“…While there is research on the patient experience of care in relation to traditional in-person models, studies on the patient experience of virtual care are limited particularly in a pandemic setting (3). Schwamm et al implemented intercoms to allow for virtual interaction with patients on the ward, however due to time constraints, were not able to design a formal study on the patient experience of engaging virtually (4).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, very little literature to date is available on patient experience during the COVID-19 pandemic and how these differ by sociodemographic characteristics. Most existing studies on patient experience during COVID-19 are from acute care, and do not stratify experience based on patient demographics [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%